Review of the diet of Icterus pustulatus (Passeriformes: Icteridae) and a new prey, Oiketicus sp. (Lepidoptera: Psychidae) from Mexico - Julián-Caballero, César Camilo (2023)
We report a case of predation on the basket worm Oiketicus sp. (Lepidoptera, Psychidae) by the Streak-backed Oriole (Icterus pustulatus) in the Municipality of Santa Cruz Xoxocotlán, Oaxaca, Mexico. The bird was photographed, and we describe the prey based on its basket, cephalic capsule, and fragments of thoracic segments. We describe the foraging strategy and provide a list of previously recorded food resources in the diet of I. pustulatus. This is the first documentation of a basket worm being consumed by I. pustulatus, which may be considered omnivorous.